The Digital Da'wah Strategy Amid the Flow of Hoax Information - Huswatun Hasanah (Journal of Scientific Studies and Multidisciplinary Research, 2024)
This study examines the application of digital da’wah strategies to counter the spread of hoax information on social media, focusing on the role of the tabayyun approach and the importance of digital literacy. In the digital era, social media has become a powerful tool for spreading Islamic teachings, but it also facilitates the rapid dissemination of misinformation, especially concerning religious matters. This research used a library research method, analyzing secondary data from academic articles, books, and reliable online sources to identify effective strategies for digital da’wah. Key findings highlight the critical role of social media in reaching a broad audience, the need for verification of information (tabayyun), and the importance of enhancing digital literacy among da’is to ensure that Islamic teachings are conveyed accurately. Furthermore, the study emphasizes the challenges of competing for attention in the digital space and the necessity for collaboration with technology platforms and other digital communities. The research concludes by recommending a comprehensive digital da’wah strategy combining verification, literacy, innovation, and collaboration to effectively address the challenges of misinformation in the digital era. Keywords: digital da’wah, hoaxes, tabayyun, social media, digital literacy.